2012
DOI: 10.1002/ccd.24657
|View full text |Cite
|
Sign up to set email alerts
|

Patients without prolonged QRS after TAVI with CoreValve device do not experience high‐degree atrio‐ventricular block

Abstract: Delayed (>24 hr after the procedure) high-grade AVB necessitating PP is common after TAVI. QRS duration measured immediately after TAVI was the best independent predictor of PP in this population. Patients with QRS ≤ 128 msec immediately after TAVI had no risk of requiring PP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 17 publications
0
11
2
1
Order By: Relevance
“…Several studies consistently revealed the relation between a too deep implantation of the prosthesis and the occurrence of new-onset LBBB and permanent pacemaker implantation. [17][18][19][20][21] In our study, such correlation emerged in the univariable analysis, but it did not show to be statistically significant in the subsequent multivariable analysis. The findings of this study are not in disagreement with those who focused on the role of depth of implantation because this study incorporated both depth of implantation and contact pressure and contact pressure area.…”
Section: Discussioncontrasting
confidence: 69%
“…Several studies consistently revealed the relation between a too deep implantation of the prosthesis and the occurrence of new-onset LBBB and permanent pacemaker implantation. [17][18][19][20][21] In our study, such correlation emerged in the univariable analysis, but it did not show to be statistically significant in the subsequent multivariable analysis. The findings of this study are not in disagreement with those who focused on the role of depth of implantation because this study incorporated both depth of implantation and contact pressure and contact pressure area.…”
Section: Discussioncontrasting
confidence: 69%
“…3 Therefore, identifying patients with a high probability of developing an AVCD and of requiring a PM is of the utmost importance. Mouillet et al 12 analyzed ''delayed'' need for a PM (more than 24 h after TAVI) in patients without previous AVCD. The only independent predictor of the need for a PM was a prolonged QRS duration, and the authors concluded that patients with a QRS of less than 128 ms after TAVI have no risk of requiring a PM.…”
Section: Timing Of Onsetmentioning
confidence: 99%
“…However, TAVI has the potential to cause complications, which can be associated with poor prognosis, including the occurrence of high‐degree atrioventricular conduction disturbance (AVCD) requiring pacemaker (PM) implantation . Although QRS duration immediately after TAVI has been reported to predict AVCD leading to PM implantation , Bjerre Thygesen et al showed that QRS duration increases progressively following TAVI, reaching a peak on days 7–9, and then decreases to near baseline values in self‐expandable device implanted patients . Moreover, some studies showed that peri‐operative high‐degree AVCD partially resolves, and the rate of electrical conduction recovery has been identified as 22–56% during follow‐up after TAVI .…”
Section: Introductionmentioning
confidence: 99%